2014
DOI: 10.1002/sia.5366
|View full text |Cite
|
Sign up to set email alerts
|

Study of the early stages of growth of Co oxides on oxide substrates

Abstract: The growth of Cobalt oxides by reactive thermal evaporation of metallic Cobalt in an oxygen atmosphere on a series of oxide substrates, namely SiO2, Al2O3 and MgO, has been chemically and morphologically studied by means of XPS and atomic force microscopy (AFM). The XPS results reveal that cobalt oxide grows as CoO (Co2+) for coverages up to some tens of equivalent monolayers on all substrates. For larger coverages, the formation of the spinel oxide Co3O4 has been observed. AFM and XPS quantification allowed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Besides, three more factors can complement this explanation helping to promote the copper oxidation: 1) metal nanoclusters tend to lose electrons and ionize; [ 51 ] 2) the reducing chemical nature of copper, which tends to reduce the oxides in contact with it becoming itself oxidized; and 3) zinc 3d orbitals are completely full, which induces less reactivity with O 2 and allows the presence of metal Zn even at such high pressures, two orders of magnitude higher than for other oxides, such as Co or Ni, using the same evaporation technique. [ 52,53 ] Thus, zinc is deposited on graphene first as a metal and only becomes oxidized once the oxidation process of copper has finished since all the intercalated species have been consumed (see Figure S2b, Supporting Information). Under this description, depending on the initial amount of intercalated species and the initial state of graphene (local work function values of graphene and copper and the initial electronic coupling between them), the thicknesses of the metal zinc deposit and the copper oxide layer can vary.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, three more factors can complement this explanation helping to promote the copper oxidation: 1) metal nanoclusters tend to lose electrons and ionize; [ 51 ] 2) the reducing chemical nature of copper, which tends to reduce the oxides in contact with it becoming itself oxidized; and 3) zinc 3d orbitals are completely full, which induces less reactivity with O 2 and allows the presence of metal Zn even at such high pressures, two orders of magnitude higher than for other oxides, such as Co or Ni, using the same evaporation technique. [ 52,53 ] Thus, zinc is deposited on graphene first as a metal and only becomes oxidized once the oxidation process of copper has finished since all the intercalated species have been consumed (see Figure S2b, Supporting Information). Under this description, depending on the initial amount of intercalated species and the initial state of graphene (local work function values of graphene and copper and the initial electronic coupling between them), the thicknesses of the metal zinc deposit and the copper oxide layer can vary.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO was deposited on both substrates in successive evaporations, the sample being analyzed in-situ by XPS after each step. A complete explanation of the procedure for the estimation of the amount of deposited material for each step can be found elsewhere [39,43]. Ex-situ AFM and Raman spectroscopy measurements were performed for a set of samples with different ZnO coverages, precisely those of interest for the characterization of the early stages of growth.…”
Section: Methodsmentioning
confidence: 99%
“…the formation of an initial CoO wetting layer followed by the growth of CoO islands. Other studies involving CoO/oxide interfaces have also been reported [9,10,11,12]. In general, cobalt oxides grow on other oxides in the form of CoO (Co 2+ ) using reactive thermal evaporation as the growth method.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, CoO grows in a Frank van der Merwe form, i.e. layer by layer mode, on Al2O3 and MgO, whereas it grows in a Volmer-Webber manner, i,e, islands mode, on SiO2 [11].…”
Section: Introductionmentioning
confidence: 99%